Tributary reform 2016 “real scopes” (2016)
he tributary national system needs a redesign that establishes a new structure, administrative officer speaking, this to initiate the economic evolution of the country, reason for which a commission of experts, designated by the government, realized a study of more than ten months, which allows to conclude a series of necessary changes relating to the mechanism of current taxation, is pertinent to clarify that the above mentioned changes are considered to be necessary and applicable to settle the public expenditure and the fiscal deficit that nowadays one presents